Delivery through cervicovaginal fistula – literature review and case report. (4th March 2019) - Watrowski, Rafał; Babbel, Burghardt; Gitsch, Gerald
Abstract: Less than 10 deliveries via cervicovaginal fistula (CVF) with closed cervical os were reported so far. In the majority of cases, the patients had a history of induced abortions. The CVF was usually recognized due to postpartum hemorrhage. The facilitating role of prostaglandins used for labor induction was supposed. In all cases, the babies remained unaffected by the delivery route. We report a new case of a 37-year-old gravida 2, para 0, with a history of a paracervical tear following a first trimester abortion 11 years ago. The abortion and the laceration were not reported in the current obstetrical documentation. After labor induction using oral misoprostol in the 41 + 5 weeks of pregnancy, the patient delivered a healthy baby through a left-sided CVF, which imposed as bleeding paracervical laceration, 6 cm in diameter, extending to the vaginal fornix in the 3 o'clock position. The cervical os was only 1–1.5 cm dilated and imposed as an inelastic band ("squid ring") in the 9 o'clock position. The laceration was sutured under spinal anesthesia. The patient recovered quickly, and the postpartum hemoglobin drop was 2.8 g/dl. In conclusion, the possibility of CVF should be considered in women with a history of induced abortion.